Testing the greenwashing assessment framework - Hill, Stephanie; Nemes, Noemi; Montgomery, A. Wren; Scanlan, Stephen; McNally, Brenda; Tubiello, Francesco; Aronczyk, Melissa; Wood, Tim; Smith, Tone; Kaupa, Clemens (Ecology and society, 2025)
Greenwashing is of growing concern as the world struggles to respond to the triple planetary crises of pollution, climate change, and biodiversity loss. New terminology to label greenwashing has entered public discourse and new policies and legal processes have challenged green claims, particularly in advertising. These developments demand a review and revision of the terminology used in greenwashing research and analysis of its application to statements made by businesses, governments, and other organizations. This paper focuses on just that, making two key academic contributions to the growing interdisciplinary literature on greenwashing. First, we empirically test, for the first time, the greenwashing assessment framework, an analytical means to assess greenwashing. Second, we build on our empirical findings to propose a revision to this framework. This testing makes an important contribution to help the public, managers, policy makers, and journalists navigate the complex information domain surrounding environmental issues.